Education Rebranding of the Police Institution: Is Police Reform Possible from the Community's Perspective? - Indah Earlyanti, Novi; Mayastinasari, Vita; Syafruddin, Syafruddin; Lubis, Rahmadsyah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The reform of the Indonesian National Police (Polri) since its separation from the Indonesian National Armed Forces (TNI) in 1999 aims to transform Polri into a professional, accountable, and humanistic law enforcement agency. However, after more than two decades, Polri's public image still faces significant challenges, including fluctuating public trust due to controversial cases and human rights violations. Reform efforts through restructuring and digital innovations, such as the Presisi program and Polri SuperApp, have not fully addressed cultural aspects and public perceptions. Public education and awareness about Polri are crucial for improving its image. Enhancing public understanding can help bridge the gap between Polri and the community, strengthening trust and cooperation. The public's awareness of Polri's efforts to uphold law and order, as well as its commitment to reform, plays a vital role in shaping a positive perception of the institution. This study emphasizes a bottom-up approach with the community's perspective serving as the foundation for Polri's rebranding. Using Legitimacy Theory, Public Trust Theory, and Institutional Branding Theory, this research aims to analyze urban community perceptions, identify the factors that shape Polri's brand, and develop a rebranding model based on public input. The results are expected to provide recommendations for a more authentic and sustainable cultural reform of Polri.